A Population Health Driver Diagram to Address Neonatal Abstinence Syndrome. Issue 6 (November 2017) - Erwin, Paul Campbell; Meschke, Laurie L.; Ehrlich, Samantha F.; Moran, John W.
Abstract : This article describes the process for developing a population health driver diagram to address a priority health issue in East Tennessee: neonatal abstinence syndrome (NAS). Population health driver diagrams are used in quality improvement processes for determining and aligning actions that a community can take to achieve a specified outcome. The Tennessee Department of Health contracted with the University of Tennessee's Department of Public Health to conduct a community participatory process to contribute to a statewide health improvement plan. Colleagues in local public health practice identified NAS as the leading perinatal health issue, and community engagement was achieved by involving community health councils. Qualitative and quantitative data were collected, analyzed, and provided to these councils. A region-wide stakeholders' meeting resulted in the development of a population health driver diagram to address NAS. We describe this process and provide lessons learned that can be valuable in other settings. Population health diagrams have important implications for practice because of their use as a framework for community action, especially in the context of a community health assessment. Abstract : Supplemental Digital Content is Available in the Text.